BIOL-04. DISTAL-LESS/DLX2 HOMEOBOX GENE REGULATION OF CHEMOKINE RECEPTOR CXCR4 - ROLE IN MIGRATION IN FOREBRAIN DEVELOPMENT AND CNS TUMORS. (23rd April 2019) - Japoni, Sara; Song, Xiaohua; Leng, Roger; Eisenstat, David
Abstract: INTRODUCTION: Diffuse intrinsic pontine glioma (DIPG) have an extremely poor prognosis. Mutations of the genes encoding histone H3K27, especially H3K27M, are highly prevalent. There is reduced expression of the homeobox gene Dlx2 in DIPG with H3K27M mutations. Single cell RNA sequencing suggests that the cell of origin is an oligodendroglial progenitor cell (OPC). DLX2 transcription factors promote GABAergic interneuron differentiation and tangential migration to the neocortex from basal forebrain structures such as the ganglionic eminences (GE) where neural progenitors and OPC both derive. We and others have demonstrated that DLX transcription factors repress OPC differentiation while activating gene networks required for interneuron differentiation and migration. We are exploring the embryonic forebrain and DIPG microenvironment and specifically the role of DLX2 regulation of CXCR4, the receptor for the chemokine CXCL12 essential for interneuron migration. RESULTS: Using chromatin immunoprecipitation of E13.5 mouse GE and our specific polyclonal DLX2 antibody, we isolated seven regions of the Cxcr4 gene promoter occupied by DLX2 in vivo . Subsequently, using electrophoretic mobility shift assays (EMSA), we determined that DLX2 specifically bound to five of these regions containing candidate homeodomain DNA binding sites in vitro . Co-transfection of Dlx2 with a luciferase reporter construct linked to these EMSA ( +) Crxcr4 promoter elements demonstrated activation of 4 regions. There was significant loss of Cxcr4 expression in the forebrains of Dlx1/Dlx2 double knockout (DKO) mice. SiRNA knockdown (KD) of Dlx2 significantly reduced Cxcr4 expression in vitro . Cell migration was significantly decreased in the presence of CXCL12 either by Dlx2 KD or by using plerixafor, a CXCR4 signaling inhibitor. CONCLUSIONS: DLX2 binds to the Crxr4 promoter and activates its expression. Pharmacological regulation of CXCR4 signaling may be an important avenue to pursue towards blocking OPC-like DIPG migration and invasion in vivo .